BAP1 regulates cell cycle progression through E2F1 target genes and mediates transcriptional silencing via H2A monoubiquitination in uveal melanoma cells. (March 2015) - Pan, Hui; Jia, Renbing; Zhang, Leilei; Xu, Shiqiong; Wu, Qing; Song, Xin; Zhang, He; Ge, Shengfang; Leon Xu, Xiaoliang; Fan, Xianqun
Abstract: Uveal melanoma (UM) is the most common form of primary intraocular malignancy in adult and has the tendency to metastasize. BAP1 mutations are frequently found in UM and are associated with a poor prognosis. The role of BAP1 in cell cycle regulation is currently a research highlight, but its underlying mechanism is not well understood. Here, we report that BAP1 knockdown can lead to G1 arrest and is accompanied by a decrease in the expression of S phase genes in OCM1 cells. Furthermore, in chromatin immunoprecipitation experiments, BAP1 could bind to E2F1 responsive promoters and the localization of BAP1 to E2F1-responsive promoters is host cell factor-1 dependent. Moreover, BAP1 knockdown leads to increased H2AK119ub1 levels on E2F responsive promoters. Together, these results provide new insight into the mechanisms of BAP1 in cell cycle regulation.